Draining, Tørlægning, Kystsikring, etc. i Danmark. Foredrag, den 13de Marts 1878. - Feilberg, P. (Tidsskrift for Landøkonomi, 2018)
Draining, Tørlægning, Kystsikring, etc. i Danmark. Foredrag, den 13de Marts 1878.